Effects of coenzyme Q10 and N-acetylcysteine on the expression of apoptotic biomarkers and histopathological findings in the permethrin-induced hepatotoxicity in rats - Nima Asadi; Alireza Shahriary; MohammadMahdi Jafarzadeh; Maryam Ghorbani; Ehsan Yavari (Caspian Journal of Environmental Sciences)
Permethrin (PMT) is a synthetic pyrethroid insecticide widely applied in the agriculture and animal husbandry industry. The current study focused on the evaluation of the oxidative damage and apoptosis induced by PMT, as well as the protective role of coenzyme Q10 and N-acetylcysteine (NAC) against PMT toxicity in the liver of male rats. In this study,  rats were divided in four groups, including G1 (control), G2 (PMT), G3 (NAC + PMT), and G4 (Q10 + PMT). Levels of malondialdehyde (MDA) and total antioxidant capacity (TAC) were measured. RT-PCR was adopted to study the expression of Bax, Bcl2, p53, Caspases-3 and -9 genes. PMT exposure significantly decreased FRAP value, whereas increased MDA content in the liver tissue (p < 0.001). While Bcl2 was downregulated (5.31-fold), permethrin increased the expression of Bax (4.84-fold), p53 (4.67-fold), Caspases-3 (6.21-fold) and Caspases -9 (6.36-fold) genes in exposed group (p<0.001). Both Q10 and NAC significantly improved FRAP values and decreased MDA level. Unlike the apoptotic genes, Bcl2 expression was significantly reversed after NAC and Q10 therapy (p < 0.001). In conclusion, PMT exposure induced oxidative stress and liver cells’ apoptosis. Q10 and NAC can mitigate toxic effects of PMT and consequently protect liver damage.